THE IMPACT OF ORGANIZATIONAL JUSTICE ON JOB ENGAGEMENT: AN APPLICATION IN HOTELS - Nuran AKŞİT AŞIK (Fırat University, 2019)
The main purpose of this study is to determinate the effects of organizational justice perceptions of hotel employees’ on job engagement. The population of the study is formed, hotel employees working in the hotel business in Balıkesir. Since the population is of accessible size, the full enumerication sample technique was used by accessing the whole population of the study. To collect data for the study, the survey technique was used and the questionnaire form was administered to the 108 employees. SPSS 15.0 statistical program was used in data analysis. Pearson product-moment correlation coefficient was computed to determine the relationships between variables and linear regression analysis was conducted to determine to what extent independent variables predict dependent variables. According to the analyzing of collected data, a significant relationship was found between organizational justice, distributive justice, process justice, interaction justice and organizational commitment at the 0,01 significant level. The level of the relationship for organizational justice and job engagement was 56%. The level of the relationship between distributive justice and engagement was 51%, between process justice and engagement was 46 %, between interaction justice and engagement was 58%. The regression analysis revealed that the organizational justice level of job engagement of employees’ by 30%. Also, distributive justice explained 17%, process justice explained 20% and interaction justice explained 33% of job engagement.